Determinants of cross-cutting discussion on Facebook: Political interest, news consumption, and strong-tie heterogeneity - Lu, Yanqin and Lee, Jae Kook (New Media & Society, 2021)
Scholarly debate persists as to whether the use of social networking sites (SNSs) encourages or discourages political discussion with people holding different opinions. Drawing on a national survey, this study focuses on Facebook and explores the predictors of cross-cutting discussion on this platform. The results reveal that political interest is positively associated with cross-cutting discussion and this relationship is mediated by the frequency of news consumption on Facebook, suggesting that Facebook use has the potential of exposing the politically attentive to dissonant views. Furthermore, the level of heterogeneity of a person’s strong-tie network is found to accentuate the mediating effect of Facebook news consumption. Implications are discussed for the impacts of Facebook use on deliberative democracy.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDYxNDQ0ODE5ODk5ODc5